Kampanye Konten Edukasi Mengurangi Sampah Plastik pada Akun Instagram @Aksikitaindonesia - Febrianisa, Winne; Yasir, Yasir (Dimar Jaya Publishing, 2024)
Social media has become a strategic tool for conveying sustainability messages in a massive and interactive way. This study aims to analyze and assess the educational content campaign on reducing plastic waste through the Instagram account @Aksikitaindonesia. The research method used is a descriptive qualitative approach with data collection techniques through content observation, semi-structured interviews with account managers, and analysis of user interaction (engagement) with posts on the theme of plastic waste reduction education. The results of the study show that consistent, informative, and visually appealing educational campaigns can increase audience awareness and participation in movements to reduce single-use plastics. Positive interactions such as comments, reposts, and an increase in followers are indicators of the success of such campaign communications.